Resilient Aquatic Food Systems Initiative Launch in Zambia - Kakwasha, Keagan; Mudege, Netsayi N. (WorldFish, 2022)
The Resilient Aquatic Food Systems Initiatives (RAqFS) focuses on research-fordevelopment to catalyze the scaling of transformative innovations, policies and approaches to support aquatic foods in delivering more sustainable and healthy diets and livelihoods within planetary boundaries by 2030. RAqFS works through five Work Packages bundled together to deliver socio-technical innovations and policy actions that deliver benefits to all five One CGIAR Impact Areas. Apart from WP1 (which includes Kenya and Malawi), RAqFS works mainly in Bangladesh, Cambodia, Ghana, India, Myanmar, Nigeria, Solomon Islands, Timor-Leste and Zambia. The RAqFS Initiative seeks to achieve five Initiative outcomes: as follows: 1. Scaling partners and stakeholders in 11 countries use data to inform at least five evidence-based investments supporting AqFs transformation. 2. Secure rights bring livelihood benefits for 100,000 small-scale actors in AqFs in Asia-Pacific and more nutritious diets for 700,000 people. 3. GESI strategies to enhance food, livelihood, and water use outcomes in multifunctional land- and waterscapes adopted by stakeholders in two Asian and two African countries. 4. At least two tilapia, carp and catfish strains demonstrate increased productivity (+30%) and better environmental performance (-25% GHG emission reduction) in one African and two Asian countries. 5. Aquatic food system labs in three countries increase national innovation systems’ ability to identify, evaluate and scale socio-technical Innovations Packages. This report focuses on the launch of the RAqFS Initiative in Zambia. In the first three years of the Initiative, Zambia is implementing only three of the five initiatives; WorkPackage 1 (Aquata), WorkPackage 3 Aquaplans and Workpackage 5 AquaLabs. These three WorkPackages contribute to Initiative Outcomes 1, 3 and 5.